PERTANGGUNGJAWABAN PIDANA DIREKSI BUMN YANG MENERIMA GRATIFIKASI - Friandolly Jorgit Tua Manik (2022)
Abstract Gratification has been regulated in Article 12B of Law no. 31 of 1999 as amended by Law no. 20 of 2001 concerning the Eradication of Corruption Crimes. This study aims to analyze the criminal responsibility of SOE directors who receive gratification and the judge's legal considerations in making a decision on corruption in the form of gratification based on Decision Number 145/Pid.Sus/TPK/2017/PN.SBY and Number 08/Pid.Sus/TPK/2020/PN Jkt.Pst. This research uses normative juridical research and uses a case approach. In this study, the sources of data taken from Law no. 20 of 2001 concerning Amendments to Law Number 31 of 1999 on the Eradication of Corruption Crimes; Law No. 40 of 2007 concerning Limited Liability Companies; Law No. 19 of 2003 concerning State-Owned Enterprises; KUHP. The results in this study found that there has been an abuse of authority by the Board of Directors by committing a criminal act of gratification. Keywords: Corruption Crime, Gratification, Directors